The Girls’ Side. Analysis of Bianca Pitzorno’s Contribution to Children’s Literature - Elena Tosi (Studia Polensia, 2017)
This essay provides an overview of the contribution of the Italian writer Bianca Pitzorno to children’s literature. This author is important on both a national and international level. She dedicated her life to writing stories with female children and teenagers as lead characters when the literature of the mostly provided them with supporting roles with weak or submissive personalities. Other literary authors wrote about girls (e.g. Carroll, Michaelis, Lindgren, Dahl and Petrosino), but none of them ever embraced this task like Pitzorno. Also if we compare some of lead male characters in classic children’s literature (ones by Calvino, Collodi, De Amicis, Kipling and Malot) with Pitzorno’s female ones, we can see that the latter are on par with their male counterparts.